Improved COVID-19 outcomes in a large non-invasive respiratory support cohort despite emergence of the alpha variant - Najib M Rahman; Robert Wilson; John M Wrightson; Nayia Petousi; Ian Pavord; Mona Bafadhel; Stephen Chapman; Rachel Hoyles; William Flight; Emily Fraser; Annabel Nickol; Dinesh Addala; et al. (BMJ Open Respiratory Research)
Introduction Respiratory high-dependency units (rHDUs) are used to manage respiratory failure in COVID-19 outside of the intensive care unit (ICU). The alpha variant of COVID-19 has been linked to increased rates of mortality and admission to ICU; however, its impact on a rHDU population is not known. We aimed to compare rHDU outcomes between the two main UK waves of COVID-19 infection and evaluate the impact of the alpha variant on second wave outcomes.Methods We conducted a single-centre, retrospective analysis of all patients with a diagnosis of COVID-19 admitted to the rHDU of our teaching hospital for respiratory support during the first and second main UK waves.Results In total, 348 patients were admitted to rHDU. In the second wave, mortality (26.7% s vs 50.7% first wave, χ2=14.7, df=1, p=0.0001) and intubation rates in those eligible (24.3% s vs 58.8% first wave, χ2=17.3, df=2, p=0.0002) were improved compared with the first wave. In the second wave, the alpha variant had no effect on mortality (OR 1.18, 95% CI 0.60 to 2.32, p=0.64). Continuous positive airway pressure (CPAP) (89.5%) and awake proning (85.6%) were used in most patients in the second wave.Discussion Our single-centre experience shows that rHDU mortality and intubation rates have improved over time in spite of the emergence of the alpha variant. Our data support the use of CPAP and awake proning, although improvements in outcome are likely to be multifactorial.